PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GROUP TO GROUP TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 6 PADANG - Handayani, Tusri; Rismen, Sefna; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background ofÂ this research were the studentsâ comprehension of mathematical concepts that still low and studentsâ less responsible for a given task. The purpose of this research was to determine whether the studentsâ comprehension of mathematical concepts by implementing active learning strategy type of Group To Group was better than studentsâ comprehension of mathematical concepts by implementing conventional learning in class XI IPA SMAN 6 Padang lesson year 2013/2014. Sampling was done randomly, which was selected XI IPA3 as the experimental class and XI IPA2 as control class. The research instrument was final test of learning that contains an indicator comprehension concept with reliability test r11 = 0.823. Hypothesis testing using the Mann-Whitney test. From the calculations, the value of z â¤ -1.9918 has a probability p = 0.0233; because the p-value was smaller than Î± = 0.05; than H0 was rejected and H1 was accepted. Based on the hypothesis test results concluded that the studentsâ comprehension of mathematical concepts by implementing active learning strategy type of Group To Group was better than studentsâ comprehension of mathematical concepts by implementing conventional learning.